Avaliação das alterações morfométricas e tempo de exposição glandular em cães com protrusão da glândula lacrimal da terceira pálpebra - Brito, Maria Caroline Pereira (2019)
Third eyelid gland protrusion is a condition of uncertain etiology, common in young dogs. It is believed that inflammation and weakening of the connective tissue that anatomically fixes the lacrimal gland to the periorbital tissues occurs, exposing it and triggering pathological changes in the glandular tissue, which will consequently interfere in the tear film production. The purpose of the study was to correlate the protrusion time of the third eyelid gland to the morphometric changes that occurred in the glandular tissue and its effects on lacrimal production. Eighteen glands of 15 dogs (eight females and seven males) with third eyelid gland protrusion were analyzed. The animals were healthy, with varying age, weight and breed. The dogs were divided into three groups according to the time of exposure of the gland. Group 1 was composed of dogs with up to six months of protrusion, Group 2, by dogs with seven to 12 months of protrusion and Group 3 by animals that had the disease for more than 12 months. In all dogs the glandular repositioning was performed using the Morgan technique. During anesteshia, immediately before surgical burial, a fragment of the gland was collected for histopathological and morphometric analysis. Group 1 presented a larger area and greater thickness of glandular acini, compared to Groups 2 and 3. Group 3 presented lower tear production according to the Schirmer test, compared to Groups 1 and 2. There was a predominance of cellular hypertrophy. Group 3 presented moderate to severe inflammatory infiltrate. No significant difference was found between groups in relation to collagen production. Exposure of the lacrimal gland of the third eyelid may reduce tear production, and this change seems to be directly proportional to the time of exposure of the gland, with atrophy of the glandular acini and decrease of the area of tear secreting tissue. Thus, the relevance of early surgical repositioning is emphasized.